Family social climate and stress in teachers of regular basic education in the province of Ilo, 2012 - Díaz Dueñas, Nora Graciela (2015)
Objective: This study set the objective of establishing the relationship between the family environment and stress on teachers of Basic Education of the province of Ilo, 2012. Method: The study was planned as correlational research with correlational no experimental design. The population was conformed by all teachers in primary and secondary schools in the province of Ilo, amounting to 1122 people initial levels. And we worked with a stratified probability sample, consisting of 232 teachers. As data collection instruments, the Family Climate Scale Moos, a scale of 90 items, which explores three dimensions were applied: family relationships, personal growth and system maintenance; and Inventory for the assessment of individual stress, an inventory of 96 items identifying the stress level based on different aspects: lifestyle, environment, symptoms, employment / occupation, relationships and personality. Results: significant relationship between family environment and stress, but with features worth noting was found. First, to analyze the possible relationship between the variables, it was found that there is negative correlation average (Rho = -0.585) between the scores achieved in the teacher rating scales of family climate variables and stress. And second, the identified correlation is highly significant (p <0.01). These data show an inverse relationship between the variables, which means that the higher the score achieved on the scale of family environment, the lower the score achieved on the stress scale. In other words, the higher is the family environment experienced by the teacher, the lower the stress disorder; and in the same manner, the lower is the family atmosphere that surrounds the teaching, the greater the stress experienced in your life. Conclusions: As a general conclusion, we found an inverse relationship between family environment and stress on teachers of Basic Education of the province of Ilo, 2012, so that the higher the family atmosphere, the lower the level stress experienced by the teac